Prevalence and burden of health problems in top-level football referees - Moen, C.; Andersen, T. E.; Clarsen, B.; Madsen-Kaarød, G.; Dalen-Lorentsen, T. (Science and Medicine in Football, 2023)
Background: Top-level football referees take decisions during strenuous physical activity, and often under great mental pressure. Despite their central role in a football match, little is known about referees` health problems, particularly in female referees. Aim: To investigate the prevalence and burden of health problems in female and male top-level referees. Study Design: Prospective cohort study. Method: Fifty-five Norwegian male and female top-level referees reported health problems (injuries and illnesses) in pre-season and during the 2020 competitive season, using the Oslo Sports Trauma Research Center Questionnaire on Health Problems (OSTRC-H2). Results: We recorded data for 49 weeks with a compliance of 98%. On average, 34% (95% CI 31-36%) of referees reported at least one health problem each week, and 20% (95% CI 19-22%) reported substantial health problems. Female referees reported more health problems than male referees, and on-field referees reported more health problems than assistant referees. Gradual-onset injuries were most prevalent and caused the greatest absence from training and matches, whereas illnesses represented only a small portion to the overall burden of health problems. The injury incidence was three injuries per athlete-year (95% CI 2.5-3.5) and 11 injuries per 1000 match hours (95% CI 7-18). The illness incidence was 1.4 illnesses per athlete-year (95% CI 1.1-1.8). Injuries to the lower legs and feet represented the highest burden of health problems. Conclusion: Top-level referees, especially females, reported a high prevalence of health problems. Gradual-onset injuries to the lower leg and foot represented the highest injury burden.